2022
DOI: 10.3390/ijerph19052966
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Online Learning on Physical and Mental Health in University Students during the COVID-19 Pandemic

Abstract: Higher education organizations have been influenced by the COVID-19 pandemic. During school closures, online teaching and learning has become a new routine that may lead to changes in lifestyles and adversely affect university students’ health. Therefore, this study was to understand the potential impact of online learning on physical and mental health by investigating the differences in physical activity, psychological distress, and student life stress in Taiwanese university students between the in-class lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…In this study, almost half, 44.85%, of the respondents had a subjective feeling that their eyesight had deteriorated since they started studying/working online, and 19.07% declared that the deterioration of their vision had been confirmed by an examination with a specialist. Also, other authors report that more than 83% of e-learning learners have some kind of ophthalmic problem, because the electronic device emits electromagnetic light that adversely affects vision [7].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, almost half, 44.85%, of the respondents had a subjective feeling that their eyesight had deteriorated since they started studying/working online, and 19.07% declared that the deterioration of their vision had been confirmed by an examination with a specialist. Also, other authors report that more than 83% of e-learning learners have some kind of ophthalmic problem, because the electronic device emits electromagnetic light that adversely affects vision [7].…”
Section: Discussionmentioning
confidence: 99%
“…Countries' "stay at home" orders, lockdown policies, or self-segregation modes have caused people, especially students, to have significantly decreased physical activities [12]. In fact, studies have clearly shown that when students are not at schools, such as during summer vacations and long weekends, they are less physically active and have longer sedentary time or screen time [13].…”
Section: The Impact Of the Decreased Physical Activitiesmentioning
confidence: 99%
“…To date, vaccinations have proven to be an effective strategy reducing the spread of the COVID-19 infection. Despite this, the pandemic notably affected various aspects of teaching and learning [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the great interest, little is known about the impact of changes in learning modalities on undergraduate students’ mental health and academic performance. In their study, the authors of [ 12 ] found no significant differences in students’ psychological distress between the face-to-face (f2f) modality and online learning. Moreover, while some studies highlighted students’ comparative preference for online learning over f2f [ 40 ], others pointed out their negative opinions of remote learning due to technical problems [ 41 ].…”
Section: Introductionmentioning
confidence: 99%